Management of Diabetes in the Intrapartum and Postpartum Patient - Dude, Annie; Niznik, Charlotte M.; Szmuilowicz, Emily D.; Peaceman, Alan M.; Yee, Lynn M. (American Journal of Perinatology, 2018)
Achieving maternal euglycemia in women with pregestational and gestational diabetes mellitus is critical to decreasing the risk of neonatal hypoglycemia, as maternal blood glucose levels around the time of delivery are directly related to the risk of hypoglycemia in the neonate. Many institutions use continuous insulin and glucose infusions during the intrapartum period, although practices are widely variable. At Northwestern Memorial Hospital, the “Management of the Perinatal Patient with Diabetes” policy and protocol was developed to improve consistency of management while also allowing individualization appropriate for the patient's specific diabetic needs. This protocol introduced standardized algorithms based on maternal insulin requirements to drive real-time maternal glucose control during labor as well as provided guidelines for postpartum glycemic control. This manuscript describes the development and implementation of this protocol to encourage other institutions to adopt a standardized protocol that allows highly individualized intrapartum care to women with diabetes.
Keywords: diabetes; intrapartum; postpartum; neonatal hypoglycemia